The jewish national and university library : its history and development. (Jerusalem, 1948)
Bibliotheek Camille Huysmans
Overdruk uit: "The Hebrew University, Jerusalem. Its history and development", 1948
Engels
Brochure
Keywords: universiteiten; Jeruzalem; Israël